Analysis of E-Wom Effectiveness in Celebrity Cancel Culture Action on Sosial Media X - Luthfiyah, Finna Nazmi (Jogjakarta Communication Conference (JCC), 2024)
This research examines the effectiveness of Electronic Word of Mouth (E-WOM) in the cancel culture phenomenon against celebrities on social media X, focusing on controversial cases involving Kpop idols and the cancel culture movement related to the "Blue" genocide. With high internet penetration in Indonesia, social media is the main platform for spreading public opinion that can shape the reputation and career of celebrities. This research method uses a qualitative approach with content analysis. Data was collected through observation of online interactions, reviews, and comments on social media X related to cancel culture on celebrities. Samples were selected based on relevant cancel culture events, with content analysis aiming to identify patterns, themes, and sentiments in online conversations. The results show that E-WOM plays a crucial role in shaping public opinion that can create significant impacts, both socially and economically, on celebrities or brands that are targeted by cancel culture. The impacts include decreased popularity, decreased financial support, and potential career losses. While cancel culture through E-WOM provides a platform for people to voice their concerns, there are debates around the potential injustice, lack of learning, and long-term impact on freedom of expression. The complexity of public opinion dynamics in the digital age and propose alternative approaches to address controversy and create constructive dialog in a digital society.